CULBAC® and ADD-F® (formic acid) additives for sudangrass and high moisture shelled corn silages - K. Bolsen; M. Hinds; H. Ilg (Kansas Agricultural Experiment Station Research Reports, 1984)
Laboratory silos were used in three trials to evaluate sudangrass (slightly or moderately wilted) and high moisture corn silages, each receiving the following treatments: (1) control (no additive); (2) CULBAC® dry; (3) CULBAC® liquid; and (4) ADD-F® (formic acid). Although the 12 silages were well preserved visually, there were differences in their chemical compositions. Silages treated with CULBAC dry had the highest DM recoveries and probably the most efficient fermentations. As expected, formic acid restricted the amount of fermentation, but surprisingly, it did not improve DM recovery.
Keywords: Cattlemen' s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Additives; Sudangrass; Corn silage